Android-Based Mobile Learning Resource for Chemistry Students in Comprehending the Concept of Redox Reactions - Nazar, Muhammad; Rusman; Puspita, Kana; Yaqin, Husnul (International Journal of Interactive Mobile Technologies (iJIM), 2022)
This study aimed to develop an Android learning media on the concept of redox as an effective, efficient, practical, real-time learning media and in accordance with the facilities owned by students and evaluate the quality and usability of the app. The approach used in this research was a quantitative approach in the form of development research, while the model used was the Hannafin and Peck (1988) model. The data of this study were collected from the process of development, expert evaluations (expert reviews), and small group evaluation. 20 students of the chemistry education study program at a university in Indonesia volunteered to use and evaluate the app, Data was collected by using questionnaires. The results indicated that the quality of the application obtained from expert review was 94.7%. Furthermore, the small group evaluation shows that the usability of RedoksPro version 1.1 scored 86.7. The Android-based learning media of redox concept (RedoksPro application version 1.1) could be utilized as a mobile learning resource in learning the specific concept of reduction and oxydation reactions.